2022
DOI: 10.1093/schbul/sbac044
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Plus Dietary Fiber Supplements Attenuate Olanzapine-Induced Weight Gain in Drug-Naïve First-Episode Schizophrenia Patients: Two Randomized Clinical Trials

Abstract: Background and Hypothesis Antipsychotic-induced weight gain is associated with alterations to the composition of the gut microbiota. The purpose of this study was to determine the effect of probiotics plus dietary fiber on antipsychotic-induced weight gain. Study Design Two sequential, randomized clinical trials were conducted. In Study 1, 90 drug-naïve, first-episode schizophrenia patients were randomized to receive either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Lactobacillus is a typical probiotic that has been widely used to enhance intestinal barrier [49], reduce visceral fat mass [50,51], maintain body weight [52], and improve glucose tolerance [53]. Recently, Lactobacillus has also been proved to be effective in curbing antipsychotics-induced weight gain in patients with SZ [17,18]. Thus, these synergistic effects may further support the potential uses of "supplementation with Lactobacillus" in antipsychotic-induced weight gain by increasing the abundance of healthy bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus is a typical probiotic that has been widely used to enhance intestinal barrier [49], reduce visceral fat mass [50,51], maintain body weight [52], and improve glucose tolerance [53]. Recently, Lactobacillus has also been proved to be effective in curbing antipsychotics-induced weight gain in patients with SZ [17,18]. Thus, these synergistic effects may further support the potential uses of "supplementation with Lactobacillus" in antipsychotic-induced weight gain by increasing the abundance of healthy bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found a potential link between gut bacteria and aberrant BMI after antipsychotic medication. Two randomized clinical trials demonstrated that modulating the gut milieu with probiotics and dietary ber could effectively ameliorate antipsychotics-induced weight gain for SZ patients [17,18], suggesting a potential link between microbial dysbiosis and metabolic disorders. Hence, we conducted a cross-sectional study to compare the gut microbiota between SZ-O and SZ-N groups.…”
Section: Microbial Changes Of Diversity and Composition In Sz-o Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this evidence, additional perspectives and interests towards the role of Bifidobacterium, Lactobacillus and Enterococcus (1 × 10 7 CFU each [46]/ ≥ 5.0 × 10 7 CFU/g [47]) in the amelioration of olanzapine-induced body weight arose [46,47]. Yang et al [46] emphasized a between-group difference, after four weeks treatment, in weight (p < 0.05) and body mass index (BMI) (p < 0.05) that lasted for eight to twelve weeks of treatment (p > 0.05) with no differences in terms of appetite during the analyzed period (p > 0.05); a non-statistical significance mean time from olanzapine initiation to appetite changes was also obtained (p = 0.22).…”
Section: Olanzapinementioning
confidence: 92%
“…Yang et al [46] emphasized a between-group difference, after four weeks treatment, in weight (p < 0.05) and body mass index (BMI) (p < 0.05) that lasted for eight to twelve weeks of treatment (p > 0.05) with no differences in terms of appetite during the analyzed period (p > 0.05); a non-statistical significance mean time from olanzapine initiation to appetite changes was also obtained (p = 0.22). Moreover, two randomized controlled trials (RCTs) conducted by Huang et al [47] have been conducted to evaluate the benefits brought by Bifico. In the first twelve-week study, no effects of the probiotics on weight gain (p < 0.005) were observed, whereas in the second study, probiotics and dietary fiber exerted a beneficial impact (p = 0.007) per insulin resistance index (IRI) value (p < 0.005/p < 0.001), particularly in olanzapine monotherapy, but not in olanzapine combined with probiotics and dietary fiber (p = 0.35).…”
Section: Olanzapinementioning
confidence: 99%